Rh2-enriched Korean ginseng (Ginseng Rh2+) inhibits tumor growth and development of metastasis of non-small cell lung cancer. Issue 17 (20th July 2021) - Lev-ari, Shahar; Starr, Alexander N.; Vexler, Akiva; Kalich-Philosoph, Lital; Yoo, Hwa-seung; Kwon, Ki-rok; Yadgar, Meital; Bondar, Ekaterina; Bar-shai, Amir; Volovitz, Ilan; Schwarz, Yehuda
Abstract : While there are multiple studies on the anti-tumoral effects of Panax ginseng as an active ingredient/s or as a whole plant extract, there is a lack of studies to assess the effect of Panax ginseng active ingredients combined with the whole plant extract. Abstract : Background and objective : While there are multiple studies on the anti-tumoral effects of Panax ginseng as active ingredients (one or more ginsenosides derived from the extract) or as a whole plant extract, there is a lack of studies to assess the effects Panax ginseng's of active ingredients combined with the whole plant extract. Our aim was to study the effect of whole ginseng, enriched in the anti-tumoral Rh2 component and other ginsenosides (Ginseng Rh2+), on the metastatic capacity of non-small cell lung cancer (NSCLC). Methods : We evaluated the effects of Ginseng Rh2+ on survival, migration and motility, induction of apoptosis, and expression of its apoptosis-related proteins in non-small cell lung cancer (NSCLC) cells in vitro and on primary tumor growth and metastatic capacity in a syngeneic mouse lung cancer model in vivo. The effects of Ginseng Rh2+ on NSCLC cells were studied in vitro using: a colorimetric tetrazolium salt (XTT) assay, annexin V-FITC/PI, western blotting, wound healing motility assay, Transwell migration and cell adhesion assays. In vivo, mice were inoculated with Lewis mouse lung carcinoma cells subcutaneously to evaluate local tumor growth, or intravenously to evaluate the effects of Ginseng Rh2+ on development of experimental metastases. Mice were treated by intraperitoneal administration of Ginseng Rh2+ (0.005–0.5 g kg −1 ) on days 6, 10, and 14 after tumor injection. Results : We found that Ginseng Rh2+ increased the apoptosis of NSCLC cells in vitro, demonstrating dose dependent down-regulation of the Bcl-2 anti-apoptotic gene and concurrent up-regulation of the Bax pro-apoptotic gene. Ginseng Rh2+ inhibited the tumor cells' capacity to attach to the ECM-related matrix and reduced cell migration. In vivo, Ginseng Rh2+ inhibited local tumor growth and reduced the development of experimental lung metastases. Conclusion : Our study suggests that Ginseng Rh2+ may potentially be used as a therapeutic agent for treatment of NSCLC.